2021
DOI: 10.1039/d1nj02536h
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free and multicomponent synthesis of 3-aminoalkylated indolesviaa Mannich-type reaction: multitargeted anticancer, tyrosinase and α-glucosidase inhibitory activities

Abstract: Highly efficient and sustainable approach for the multi-component synthesis of 3-aminoalkylated indoles was investigated via Mannich-type reaction under catalyst-free, methanol and ethylene glycol (EG) as promoting media. Synthesizing various substrates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Their therapeutic target is peroxisome proliferator-activated receptor-γ (PPARγ). Recently, TZD derivatives have been reported to be potent inhibitors against tyrosinase, such as benzylidene-TZD derivatives (Figure 1D) [28] and 2,4-dihydroxybenzylidene-TZD (Figure 1E) [29]. The above analysis suggests that TZD can also serve as a core framework for designing potential tyrosinase inhibitors.…”
Section: Introductionmentioning
confidence: 83%
“…Their therapeutic target is peroxisome proliferator-activated receptor-γ (PPARγ). Recently, TZD derivatives have been reported to be potent inhibitors against tyrosinase, such as benzylidene-TZD derivatives (Figure 1D) [28] and 2,4-dihydroxybenzylidene-TZD (Figure 1E) [29]. The above analysis suggests that TZD can also serve as a core framework for designing potential tyrosinase inhibitors.…”
Section: Introductionmentioning
confidence: 83%
“…(NR 2 =pyrrolidin‐1‐yl, R 1 =Br, R 2 =H, R 3 =4‐H 3 COC 6 H 4 ) was 4 to 15 times less potent than camptothecin against A549, MDA‐MB‐231 and PC‐3 cell lines [135] . Reaction of SN38 (a metabolite of irinotecan) with pyrrolidine under the conditions for Mannich reaction occurred at C‐5 to give compound 133 (Figure 17) as a mixture of diastereomers, whose activities against MCF‐7 (IC 50 ∼0.9 μM), HT‐29 (IC 50 ∼0.05 μM), HL‐60 (IC 50 ∼0.01 μM) and A549 (IC 50 ∼0.3 μM) cancer cell lines were good and comparable, albeit inferior to that of parent SN38 [136] .…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Obtained ...mentioning
confidence: 99%
“…[134] Evaluation of a series of Mannich bases 132 of indoles (Figure 17) showed that the best compound in the series (NR 2 = pyrrolidin-1-yl, R 1 = Br, R 2 = H, R 3 = 4-H 3 COC 6 H 4 ) was 4 to 15 times less potent than camptothecin against A549, MDA-MB-231 and PC-3 cell lines. [135] Reaction of SN38 (a metabolite of irinotecan) with pyrrolidine under the conditions for Mannich reaction occurred at C-5 to give compound 133 (Figure 17) as a mixture of diastereomers, whose activities against MCF-7 (IC 50 ~0.9 μM), HT-29 (IC 50 ~0.05 μM), HL-60 (IC 50 ~0.01 μM) and A549 (IC 50 ~0.3 μM) cancer cell lines were good and compara-ble, albeit inferior to that of parent SN38. [136] Imidazo[1,2a]pyrimidines have been used as substrates in aminomethylation for the generation of a collection of mono-Mannich bases 134 and bis-Mannich bases 135 (Figure 17), and several compounds in this collection are potent growth inhibitors of A-549 human epithelial lung carcinoma, HeLa cervical cancer cells, PANC-1 pancreatic cancer cells, or MDA-MB-231 breast adenocarcinoma.…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Obtained ...mentioning
confidence: 99%